Repurposing beta-blockers for combinatory cancer treatment: effects on conventional and immune therapies - Massalee, Rachel; Cao, Xuefang (Frontiers in Pharmacology, 2024)
Beta-adrenergic receptor signaling regulates cellular processes associated with facilitating tumor cell proliferation and dampening anti-tumor immune response. These cellular processes may lead to compromised tumor control and cancer progression. Based on this ramification, Beta-blockers (BBs) have emerged as a potential treatment by inhibiting beta-adrenergic receptor signaling. This review aimed to investigate the relationship between the use of BBs and tumor progression and treatment response. Therefore, the authors explored several aspects: the potential synergistic relationship of BBs with chemotherapy and immunotherapy in enhancing the effectiveness of chemotherapeutic and immunotherapeutic treatments and their role in boosting endogenous immunity. Further, this review explores the distinctions between the major types of BBs: Nonselective Beta Blockers (NSBBs) and Selective Beta Blockers (SBBs), and their contributions to combinatory cancer treatment. In this review, we presented a perspective interpretation of research findings and future directions. Overall, this review discusses the potential and challenge that BBs present in improving the effectiveness and outcome of cancer treatment.